Adaptasi Siswa dari Pembelajaran Daring ke Pembelajaran Tatap Muka di Era Adaptasi Kebiasaan Baru (Studi Kasus: Siswa Kelas XI IPS SMA Negeri 1 Kecamatan Guguak Kabupaten Lima Puluh Kota) - Yeli Oktavia; Wirdanengsih Wirdanengsih (Naradidik: Journal of Education and Pedagogy, 2022)
This research was motivated by the Government's policy of issuing a Joint Decree of 4 Ministers, namely the Minister of Education and Culture, the Minister of Religion, the Minister of Health, and the Minister of Home Affairs Number 03/KB/202l, Number 384 of 2021 regarding Guidelines for the Implementation of Learning in the 2019 Coronavirus Disease Pandemic. With the issuance of this policy, education has changed from online learning to face-to-face learning. SMA Negeri 1 GugAdaptation,uak District is one of the schools that has implemented face-to-face learning in the era of adapting new habits. With the change in education, students must adapt from online learning to face-to-face learning in the era of adapting new habits. This study aims to analyze according to the reality that occurs in the field regarding the adaptation of students from online learning to face-to-face learning in the era of adaptation of new habits. This study was analyzed using Talcott Parson's Structural Functional theory. This theory explains that in order for a group to survive, 4 things are needed, namely Adaptation (adaptation), Goal Attainment (achievement of goals), Integration (integration) and Latency (maintenance of patterns). This research was conducted using a qualitative approach with an intrinsic case study type. In determining the research informants, this study used a purposive sampling technique with 10 informants consisting of 1 principal, 1 subject teacher and 8 students of class XI IPS SMA Negeri 1 Guguak District. Data collection techniques using participant observation techniques, in-depth interviews and documentation studies. The validity of the data is done by data triangulation. For the data analysis technique, the researcher uses the data analysis model according to Miles and Huberman which consists of data reduction, data presentation and conclusions or verification. The results showed that the adaptation of students from online learning to face-to-face learning there were 3 adaptations, namely, 1) adaptation of rules, such as rules for bringing supplies to school and rules for dressing, 2) adaptation in the use of technology, namely cell phones, 3) adaptation in social interaction with other students.